Propagation of new dynamics of longitudinal bud equation among a magneto-electro-elastic round rod - Khater, Mostafa M. A.; Jhangeer, Adil; Rezazadeh, Hadi; Akinyemi, Lanre; Akbar, M. Ali; İnç, Mustafa (World Scientific Publ Co Pte Ltd, 2021)
In this survey, structure solutions for the longitudinal suspense equation within a magneto-electro-elastic (MEE) circular judgment are extracted via the implementation of two one-of-a-kind techniques that are viewed as the close generalized technique in its field. This paper describes the dynamics of the longitudinal suspense within a MEE round rod. Nilsson and Lindau provided the visual proof of the arrival concerning longitudinal waves within thin metal films. They recommended removal of anomalies between the ports concerning emaciated (congruent to 100 angstrom) Ag layers preserved on amorphous silica because of being mildly p-polarized at frequency tier according to the brawny plasma frequency. Anomalies have been due to confusion over the longitudinal waves mirrored utilizing the two borders. The wavelength is connected according to this wave's property, which is an awful lot smaller than the wave over light. The wave is outstanding only for altogether superfine films. However, metallic movies defended amorphous substrates that are intermittent within the forward levels of their evolution. This made researchers aware of the possibility on getting ready altogether few layers with a desire to discussing the promulgation about longitudinal waves up to expectation colorful each among reverberation or transport on p-polarized light. The mated options via the use of generalized Riccati equation mapping method or generalized Kudryashov technique show the rule and effectiveness regarding its methods then its ability because of applying one kind of forms over nonlinear incomplete differential equations.
Keywords: Longitudinal wave equation; magneto-electro-elastic circular rod; generalized Riccati equation mapping method; generalized Kudryashov method; exact and solitary traveling wave solutions